Ap(ϕ) Weights, BMO(ϕ), and Calderón-Zygmund Operators of ϕ-Type - Ruimin Wu; Songbai Wang (Journal of Function Spaces)
We introduce new classes of weights and BMO functions associated with a nondecreasing function ϕ of upper type β with β>0 and obtain the weighted norm inequalities for Calderón-Zygmund operators of ϕ-type and their commutators.